TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK PERJANJIAN TRANSAKSI UPAH â€œPACAK HEWANâ€ (Studi Atas Pacak Kucing di Comba Cattery Cinde Kota Palembang) - Dessy Carolina; Muhammad Harun; Fatah Hidayat (Universitas Muhammadiyah Surabaya, 2023)
This research is field research that aim to review of Sharia Economic Law on the agreement of Wage transaction â€œPacak Hewanâ€. The existence of cattery and petshop that provide the services of competent cat breeding. However, the practices were contrary to the prophetic tradition of Rasulullah SAW that forbade lending male cats to breed the female cats and get the wage from the breeding result, Wage transaction of cat breeding can be categorized as a transaction that contain elements of gharar because the amount of the object is not known with certainty. Therefore, additional research into this transaction is required. The research method used is the qualitative method and the type of research is the field research. The technique of data collection is by means of the method of interview, observation, and documentation, while the technique of data analysis used the qualitative analysis; data presentation and conclusion taking. The result of this research is that the Practice of Catering Transaction Agreement that occurred in Comba Cattery Cinde Palembang has not fulfilled the pillars and conditions if using a rental contract based on the hadits narrated by Abu Daud, Imam Tirmidzi and opinions from the Hanafiyah and Syafi'iah Madzhabs because what is desired from the lease it is an animal sperm. However, the solution given by Imam Syafi'i can also be used as a consideration for cattery managers to continue to carry out breeding by hiring bulls if it becomes tradition but the payment of wages by tenants is based on an expression of gratitude, not in return for rent.Keywords: Wage Transaction, Agreement, ShariaÂ Economic Law.